Students' awareness about the features of the modern labor market in the sports field - Kremneva V.N. ,; Solodovnik E.M. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the level of students’ awareness of the professional labor market in the sports field. Methods and structure of the study. In the course of scientific work, the most promising directions for the development of the sphere of physical culture and sports were identified; to study the level of awareness of students of the Institute of Physical Culture, Sports and Tourism (IPCS&T) of Petrozavodsk State University (PetrSU) about the representation of the spheres of physical culture in the economic space of Russia, their (spheres) demand and prospects. When conducting the study, the authors used general scientific approaches and research methods: description, generalization, systematic and comparative analysis and questioning. 142 IPCS&T students from 1st to 4th years in the following areas of training took part in the survey: physical education, life safety and physical education and adaptive physical education. Results and conclusions. It has been established that the most popular areas of services in the field of physical culture and sports are services in the field of medicine and healthcare, but the most profitable currently is the information sector. The survey results showed that only 6.3% of respondents would choose this field to build a future career, while the largest proportion of students plan to work in the field of education, although they recognize it as the least profitable.